Uruk, Irak. Wissenschaftliche Forschungen und Konservierungsarbeiten. Die Arbeiten der Jahre 2020 bis 2022 - van Ess, Margarete; Haibt, Max; Issa, Mayssoun; Mühl, Simone (e-Forschungsberichte des DAI, 2022)
Scientific fieldwork in Uruk, which has been resumed in 2015, as well as conservation measures on excavated structures open to visitors, were suspended between spring 2019 and late autumn 2020, initially due to unclear political conditions, then because of the worldwide restrictions caused by the COVID 19 pandemic. The period without field campaigns was used for the processing of previous findings and analyses as well as, in particular, the preparation of the publication of the pottery from Uruk. In addition, the existing digital topographical data were converted into a three-dimensional topographical model in such a way that it can be used for further analyses and visualisations of the previous excavation findings. However, the very wet winters of 2018/19 and 2019/20 had highly destabilised one structure, the ›stone building‹ at the foot of the ›Anu-Zikkurrat‹. The decision was taken to completely backfill the building as an emergency protective measure. This was carried out by the Iraqi-German conservation team despite Covid lockdowns in the autumn of 2020. In the autumn of 2021, further conservation measures followed on the ›Anu-Zikkurrat‹, which led to important additional scientific findings about the structure. In spring 2022, a short archaeological field campaign was possible, the main task of which was the emergency salvage of an almost completely preserved boat from around 2000 BC.